2023
DOI: 10.1158/1078-0432.ccr-22-3335
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 Foci as a Biomarker Predictive of Platinum Chemotherapy Response in Ovarian Cancer

Abstract: Purpose: To determine the ability of RAD51 foci to predict platinum chemotherapy response in high-grade serous ovarian cancer (HGSOC) patient-derived samples. Experimental Design: RAD51 and γH2AX nuclear foci were evaluated by immunofluorescence in HGSOC patient-derived cell lines (n=5), organoids (n=11), and formalin-fixed, paraffin-embedded tumor samples (discovery n=31, validation n=148). Samples were defined as RAD51-High if >10% of geminin-positive cells had ≥5 RAD51 foci. Associations between RAD5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…For instance, Compadre et al. showed the feasibility and consistency of RAD51 IF across different sample types, such as cell lines, organoids, and FFPE samples ( 33 ). Pikkussari et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Compadre et al. showed the feasibility and consistency of RAD51 IF across different sample types, such as cell lines, organoids, and FFPE samples ( 33 ). Pikkussari et al.…”
Section: Discussionmentioning
confidence: 99%
“…RNF24, encoding an integral membrane protein with a RING-type zinc finger, correlates with immune cell infiltration in various cancers, including OC [Yu et al, 2021]. RAD51, involved in homologous recombination and DNA repair, is crucial for platinum chemotherapy response and survival in ovarian cancer [Compadre et al, 2023], and defects in RAD51 trigger a STING-mediated innate immune response, emphasizing its role in genomic stability [Bhattacharya et al, 2017]. In the mesenchymal subtype, the transmembrane signaling enzyme PLCG2 is identified by MORE as a hub gene.…”
Section: More Insights For Hgsoc-tcga Datamentioning
confidence: 99%
“…Selection of patients for treatment with a poly (adenosine diphosphate–ribose) polymerase (PARP) inhibitor is currently based on germline BRCA1/2 ( BRCA1 , OMIM 113705; BRCA2 , OMIM 600185) mutation status for breast cancer or platinum sensitivity, BRCA1/2 alteration, or genomic HRD for ovarian cancer . Regarding functional assays of HRD, studies have shown that the RAD51 assay can effectively identify tumors with HRD that are sensitive to platinum and PARP inhibitors, albeit this functional assay has not yet been validated for treatment selection …”
Section: Introductionmentioning
confidence: 99%